Reproduction of cultural identities among amalgamated Malay and Javanese families: Enculturation, negotiation, and hybrid identities - Syafrini, Delmira; Permata, Bunga Dinda; Amelia, Lia; Febriani, Eka Asih; Saputri, Fadilla (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2023)
This article discusses how the reproduction of cultural identity in amalgamated families among Malay and Javanese in Tanjung Uma Village, Lubuk Baja District, Batam, Indonesia. The Malay and Javanese are ethnic groups that have different cultural characteristics, so various forms of negotiation are needed in the formation of cultural identity among family members. This is qualitative research with case study method, using observation and in-depth interviews with 15 informants. We use theory of location of culture by Homi K Bhabha and Stuart Hall's cultural identity to explain that cultural identity is not something rigid and standard but can be produced and reproduced. The research show that in amalgamated families of Malay and Javanese, there is a negotiation of cultural identity, making an impact on the formation of a hybrid identity in which the various elements of the two cultures adapt to each other. Hybrid identity is a form of cultural identity reproduction, the result of negotiations between the innate cultures of the two parents, as well as the dominant culture prevailing in the location where the family internalizes itself. This cultural negotiation is also the reason for the survival of Malay and Javanese amalgamated families, in the midst of high divorce rates among other ethnic amalgamation marriage in Tanjung Uma.